Pengaruh Hypnobreastfeeding Terhadap Produksi ASI - Pratiwi, Yopi Suryatim; Handayani, Sri; Alfarizi, Lalu Mariawan (Jurnal Kesehatan Qamarul Huda, 2018)
Infant mortality is still high in Indonesia. 53% is caused by nutritional factors. Exclusive breastfeeding can reduce infant morbidity and mortality. Breastmilk production is less a complaint that is most often expressed by postpartum mothers and is the cause of exclusive breastfeeding failure. This study is a literature review that attempts to explore the influence of hypnobreastfeeding on breast milk production. A review of seven studies shows hypnobreastfeeding can increase milk production. This is because hypnobreastfeeding makes the mother more relaxed, calm physically, mindfully, and comfortably during breastfeeding so that it can provide a positive feedback mechanism in the form of a response to increased release of oxytocin and prolactin by pituitary. The prolactin hormone plays a role in stimulating nutrients for the synthesis of milk in the cells of the alveoli secretory. Oxytocin causes myoepithelial contractions around the alveoli and secretes milk.